2021
DOI: 10.1186/s12885-021-08759-8
|View full text |Cite
|
Sign up to set email alerts
|

Pyrotinib combined with thalidomide in advanced non-small-cell lung cancer patients harboring HER2 exon 20 insertions (PRIDE): protocol of an open-label, single-arm phase II trial

Abstract: Background Standard therapy for human epidermal growth factor receptor 2 (HER2)-mutant non-small-cell lung cancer (NSCLC) is lacking. The clinical benefits with pan-HER inhibitors (afatinib, neratinib, and dacomitinib), anti-HER2 antibody drug conjugate (ADC) trastuzumab emtansine, and an emerging irreversible tyrosine kinase inhibitor (TKI) poziotinib were modest. Another new ADC trastuzumab deruxtecan showed encouraging outcomes, but only phase I study was completed. Pyrotinib, another emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition to antibody drugs, several small-molecule HER2 kinase inhibitors, including pyrotinib and lapatinib, are available approved agents for patients with HER2-positive breast cancer. Besides, pyrotinib has demonstrated a good potential to treat advanced NSCLC with ERBB2 mutations, especially the ERBB2 exon 20 insertions, in the phase II studies ( 40 , 41 ). In view of their drug mechanisms which bind to the HER2 kinase domain, pyrotinib or lapatinib can be a potential option for cancer patients with ERBB2 fusions, especially those X-ERBB2 fusions, which needs to be prospectively explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antibody drugs, several small-molecule HER2 kinase inhibitors, including pyrotinib and lapatinib, are available approved agents for patients with HER2-positive breast cancer. Besides, pyrotinib has demonstrated a good potential to treat advanced NSCLC with ERBB2 mutations, especially the ERBB2 exon 20 insertions, in the phase II studies ( 40 , 41 ). In view of their drug mechanisms which bind to the HER2 kinase domain, pyrotinib or lapatinib can be a potential option for cancer patients with ERBB2 fusions, especially those X-ERBB2 fusions, which needs to be prospectively explored.…”
Section: Discussionmentioning
confidence: 99%
“…role in cancer control. One recent study found that adding thalidomide to pyrotinib increased clinical benefit for advanced non-small-cell lung cancer (NSCLC) patients with HER2 exon 20 insertions, with reductions in the incidence of pyrotinib-related diarrhea (15). In a breast cancer murine model, Yang Jin et al found that thalidomide inhibited breast tumor growth through inhibition of angiogenesis by reducing tumor-associated macrophage accumulation and infiltration and decreasing angiogenesis-related cytokine production (14).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that have shown thalidomide to be immunomodulatory, to have anti-angiogenic activities that may suppress tumor growth ( 12 14 ), and to play an important role in cancer control. One recent study found that adding thalidomide to pyrotinib increased clinical benefit for advanced non-small-cell lung cancer (NSCLC) patients with HER2 exon 20 insertions, with reductions in the incidence of pyrotinib-related diarrhea ( 15 ). In a breast cancer murine model, Yang Jin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cereblon (CRBN) is a substrate adaptor in the CRL4 CRBN E3 ubiquitin ligase complex, that alters the substrate specificity of the complex following binding with IMiDs [ 17 , 18 , 19 ]. The binding of IMiDs to CRBN results in the ubiquitination and degradation of several factors, including the IKZF1 and IKZF3 transcription factors [ 20 , 21 ]. The degradation of these factors inhibits the survival and progression of MM cells [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%